2015
DOI: 10.1590/s0100-204x2015000700005
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de plantas de cobertura na floração e na maturação fisiológica e seu efeito na produtividade do milho

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito do manejo de plantas de cobertura na floração e na maturação fisiológica sobre a produtividade do milho cultivado em sucessão. O experimento, em delineamento de blocos ao acaso com parcelas subdivididas, foi realizado em Latossolo Vermelho, em sistema plantio direto, com nove espécies. Foram avaliados: produtividade de matéria seca; tempo de ciclagem dos resíduos vegetais; teores de N das plantas de cobertura; e produtividade de grãos e teores de N nas fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
25

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
1
23
0
25
Order By: Relevance
“…Annual emissions of CO 2 -C were also higher with the use of legumes than with natural fallow under both management systems, as shown by the averages obtained for conventional tillage and no-tillage, respectively: 19 and 21 Mg CO 2 -C ha -1 per year for plots with legumes versus 15 and 16 Mg CO 2 -C ha -1 per year for plots with natural fallow. The N contents of C. juncea (91 kg ha -1 N) and M. pruriens (94 kg ha -1 N), when cut at the flowering stage, are significantly higher than those of natural fallow (59 kg ha -1 N), which may explain the higher annual emissions of NO x -N + N 2 O-N and CO 2 -C from plots with legumes as cover crops (Carvalho et al, 2015). Mitchell et al (2013), while studying the effects of cover crops on N 2 O emissions, found that available mineralizable C can also control N 2 O emissions from the soil and, consequently, that C from cover crop residues can increase these emissions.…”
Section: Resultsmentioning
confidence: 94%
“…Annual emissions of CO 2 -C were also higher with the use of legumes than with natural fallow under both management systems, as shown by the averages obtained for conventional tillage and no-tillage, respectively: 19 and 21 Mg CO 2 -C ha -1 per year for plots with legumes versus 15 and 16 Mg CO 2 -C ha -1 per year for plots with natural fallow. The N contents of C. juncea (91 kg ha -1 N) and M. pruriens (94 kg ha -1 N), when cut at the flowering stage, are significantly higher than those of natural fallow (59 kg ha -1 N), which may explain the higher annual emissions of NO x -N + N 2 O-N and CO 2 -C from plots with legumes as cover crops (Carvalho et al, 2015). Mitchell et al (2013), while studying the effects of cover crops on N 2 O emissions, found that available mineralizable C can also control N 2 O emissions from the soil and, consequently, that C from cover crop residues can increase these emissions.…”
Section: Resultsmentioning
confidence: 94%
“…Lázaro et at. (2013) Coberturas mortas de inverno e controle químico sobre plantas daninhas na cultura do milho (CARVALHO et at., 2015). Para as coberturas de aveia-preta e nabo-forrageiro não foi necessário o uso de herbicidas para que a produtividade da cultura do milho maximizasse, porém para coberturas mortas de trigo, chícharo, tremoço e no pousio foi necessária uma pulverização dos herbicidas (paraquat + diuron) em pós-emergência para que se obtivesse elevado rendimento na produtividade de grãos de milho.…”
Section: Resultsunclassified
“…Considerando que a produtividade de FS obtidas pelo guandu-anão e milheto foi adequada para região do Cerrado, esses valores contrapõem a outros estudos desenvolvidos na região, em que foram constatadas produtividades inferiores para essas duas espécies (KLIEMANN et al, 2006;CALVO et al, 2010;TORRES et al, 2014;CARVALHO et al, 2015). Entretanto, também existem relatos de produtividades superiores de FS (CARNEIRO et al, 2008;RODRIGUES et al, 2012;ARAÚJO et al, 2015).…”
Section: Discussionunclassified